Pengelolaan Emisi Karbon Akibat Perubahan Tutupan Lahan Kota Pekanbaru - Arsy Dian Puspita Sari; Aryo Sasmita; Gunadi Priyambada (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Changes in land cover are the most important factors causing global environmental change. This land cover change causes an increase in gases, especially CO2 gas in the atmosphere, thus becoming one of the causes of carbon gas emissions. The study site is located in Pekanbaru City which is the capital city of Riau Province with a relatively rapid rate of regional development because it is a strategic area. The purpose of this study was to analyze the land cover change of Pekanbaru City in the period 2011–2020 and analyze the value of carbon emissions resulting from changes in land cover. The method used to analyze the value of carbon emissions is the IPCC method. In 2011, the largest land cover was dry land agriculture with an area of 27,31%, plantations covering an area of 24,76%, and settlements covering an area of 24,54% of the entire Pekanbaru City. In 2020, the area of dry land agriculture decreased drastically to 0%, while plantations experienced a fairly high increase in area to 36,07%, and settlements also experienced an increase in area to 51,32%. As a result of land cover changes in Pekanbaru City, for 10 years the estimated value of carbon sequestration is higher than the value of carbon emissions. The carbon absorption value of Pekanbaru City in the 2011–2020 period is 4,879,901,455 tons CO2-eq, while the carbon emission value of Pekanbaru City in the 2011–2020 period is 710,370,804 tons CO2-eq. The highest carbon stock value for each land cover class in Pekanbaru City for the 2011–2020 period, was in 2020 with a carbon stock value of 2,413,271 tons/year.Keywords: carbon absorption, carbon dioxide, carbon emissions, land cover change, Pekanbaru city.